Ligand binding and activation of the CGRP receptor. (20th July 2007) - Conner, A.C.; Simms, J.; Barwell, J.; Wheatley, M.; Poyner, D.R.
Abstract : The receptor for CGRP (calcitonin gene-related peptide) is a heterodimer between a GPCR (G-protein-coupled receptor), CLR (calcitonin receptor-like receptor) and an accessory protein, RAMP1 (receptor activity-modifying protein 1). Models have been produced of RAMP1 and CLR. It is likely that the C-terminus of CGRP interacts with the extracellular N-termini of CLR and RAMP1; the extreme N-terminus of CLR is particularly important and may interact directly with CGRP and also with RAMP1. The N-terminus of CGRP interacts with the TM (transmembrane) portion of the receptor; the second ECL (extracellular loop) is especially important. Receptor activation is likely to involve the relative movements of TMs 3 and 6 to create a G-protein-binding pocket, as in Family A GPCRs. Pro 321 in TM6 appears to act as a pivot. At the base of TMs 2 and 3, Arg 151, His 155 and Glu 211 may form a loose equivalent of the Family A DRY (Asp-Arg-Tyr) motif. Although the details of this proposed activation mechanism clearly do not apply to all Family B GPCRs, the broad outlines may be conserved.